62 Outcomes of delayed sternal closure in paediatric patients underwent cardiac surgery in our lady's children'hospital crumlin. (October 2018) - Khan, A; Kane, G; Mohamed, S; Elrih, M; Yamin, M; Vondrys, D; Weedle, R; Kis, B; Abdelrahaman, E; Nolke, L; Redmond, M; McGuinness, J
Abstract : Background: DSC (delayed sternal closure) is most frequently utilized in neonates and infants undergoing complex repairs. In the early days of cardiac surgery, primary closure of the sternum at the end of the operation was mandatory because of the concern of mediastinal infection. Potential risks of delayed sternal closure include sepsis, mediastinitis, bleeding, and late sternal instability. Does longer duration before DSC increase the risk of adverse outcomes or mitigate the negative effect of other risk factors? To assess this, we checked the outcomes of delayed sternal closure in our centre. Methods: We did retrospective study. All patients were studied who required delayed sternal closure post cardiac surgery in our centre in Our Lady's Children' hospital Crumlin between March 2010 and March 2017. Results: Total 3737 procedures to repair congenital cardiac anomalies were done between March 2010 and March 2017. 199 patients required delayed sternal closure (5.32%). Among these patients, 123 patients (61.81%) were male and 76 patients (38.19%) were female. Mean body weight at the time of surgery was 4.8 kg (median 3.6 kg). There were different types of primary cardiac surgeries performed. Truncus arteriosus repair was done in 13 patients (6.5%).59 patients (29.6%) were having arterial switch operation. In eight patients (4.0%) TAPVD repair was done. AVSD repair was done in eight patients (4.0%).19 patients (9.5%) were having IAA repair. Norwood procedure was done in 49 patients (24.6%). In 13 patients, Tetralogy of Fallot repair was done. Mean total cross clamp time was 103 min. Mean circulatory arrest time was 10.87 min. 62 patients (31%) required ECMO after primary surgery. Duration of mean days of sternum remained open was 3.6 days (88 hours). 52 patients (26.1%) were having positive culture. 24 patients (12.1%) required antibiotics more than 10 days. Mean stay in ICU was 17.2 days (413 hours). Overall mortality was 7 patients (8.5%) and 182 patients (91.5%) were alive (figure 1). Conclusion: Delayed sternal closure is an important strategy for congenital cardiac surgery, particularly for very young infants. Elective delayed sternal closure does not reduce the morbidity but it confirms the efficacy of the cardiac procedure. Instead of delayed sternal closure in case of ECMO, cannulation through neck vessels by experienced hands with closed sternum may be preferred.